Epic fantasy painting in oils. Part 2 - Sass, Mike; Soundview Media Partners ([Edmonton, Alberta] : Mike Sass, 2018)
"Epic Fantasy Painting in Oils" is the only film produced that teaches game-industry artwork in a traditional manner. These techniques skirt the boundary between fine and commercial art and are valuable lessons for any painter who wishes to work realistically. --
Originally released as a motion picture in 2018.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 30, 2020)
Keywords: Sass, Mike; Painting -- Technique; Fantasy in art; Fantasy comic books, strips, etc. -- Illustrations; Illustration of books -- Themes, motives; Documentary films; Nonfiction films; Internet videos; Instructional films; Streaming video